Analysis of the Perceptions of Student-Athletes Playing In the Universities Volleyball 2nd League in Turkey towards the Event Quality, - Atalay, A., Akbulut, A.k., Karataş, Ö., Hacıcaferoğlu, S., Yücel, A.s., (My University, 2015)
The purpose of this research is to analyze the perceptions of student-athletes who played in Universities Volleyball Second League competitions held in Antalya on 16th-27th December 2014 towards the event quality. Target population of the study is composed of the student-athletes studying in universities in Turkey and playing in the volleyball teams of universities at the same time, and the sample group of the study is composed of 23 student-athletes from different universities who participated in Universities Volleyball Second League held in Antalya on 16th-27th December 2014. With the purpose of determining the perceptions of student-athletes towards quality, the participants were applied a survey. SPSS (Statistical Package for Social Sciences) for Windows 21.0 program was used in the analysis of data. Descriptive statistics, t-test for determining the difference between two groups, One-way Anova test for comparisons of more than two groups and post-hoc test for group differences were used. In conclusion, it has been determined that the quality perceptions of the participants regarding the event held are positive. It has also been demonstrated that there are differences in the quality perceptions of the participants by their families’ educational background; however, a significant difference hasn’t been observed by age, sex, grade point average and income level.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Volleyball; Quality Perception; Universities Volleyball Second League